METHODOLOGICAL REQUIREMENTS FOR TEACHING COMPUTER LINGUISTICS THROUGH INTELLECTUAL MAPPING - Mamirov Ozodjon (Web of Journals Publishing, 2023)
It is known that the 21st century will be the century of rapid development of computer technologies, advanced pedagogy and information technologies (internet), high thinking, science and technology. By the beginning of the 21st century, "Electronic education", "Electronic management", "Open education", "Distance education", "Information education", "Innovative education", "Innovative pedagogical technology" concepts are getting embedded in our life day by day. In the words of President Sh.M. Mirziyoyev, "In the current age of information, communication, and computer technologies, when the Internet is getting deeper and wider into all aspects of our lives day by day, the struggle for people's consciousness and thinking is of crucial importance. in the current situation, there is no need to talk about how urgent and priority these issues are becoming for our society."